2018
DOI: 10.1007/s11255-018-1893-y
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic renography in hydronephrosis: a retrospective single-center study

Abstract: The combination of ultrasound and MAG provides the necessary anatomical and functional information to follow the degree of obstruction and to decide between surgical intervention and conservative follow-up. Our study supports a threshold of 20 mm rather than 15 mm for severe obstruction and a low DRF. An APD threshold greater than 15 mm did not have a predictive value in DRF estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
2
11
0
1
Order By: Relevance
“…Moreover, clinical variables of the enrolled patients, such as age, sex, weight, operating side of UPJO and hydronephrosis, hospital stay, duration of surgery, and complications in double-J stent placement, were collected and independently reviewed by two authors (Haobo Zhu and Jun Wang). The inclusion criteria for the patients were as follows: (1) patients diagnosed with congenital unilateral or bilateral UPJO with severe hydronephrosis (Grades II, III, and IV) as confirmed by ultrasound and/or nuclear scan; (2) patients aged between 0 and 17 years; (3) patients who had undergone LP procedures and insertion of double-J stents post-surgery; and (4) patients who volunteered to be included in this study.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, clinical variables of the enrolled patients, such as age, sex, weight, operating side of UPJO and hydronephrosis, hospital stay, duration of surgery, and complications in double-J stent placement, were collected and independently reviewed by two authors (Haobo Zhu and Jun Wang). The inclusion criteria for the patients were as follows: (1) patients diagnosed with congenital unilateral or bilateral UPJO with severe hydronephrosis (Grades II, III, and IV) as confirmed by ultrasound and/or nuclear scan; (2) patients aged between 0 and 17 years; (3) patients who had undergone LP procedures and insertion of double-J stents post-surgery; and (4) patients who volunteered to be included in this study.…”
Section: Patientsmentioning
confidence: 99%
“…1 Congenital UPJO serves as a prime indicator during the pathogenesis of hydronephrosis, which is an ailment that is twice as common in boys than in girls. 2 Moreover, hydronephrosis caused by UPJO can lead to progressive renal impairment and further renal failure if left untreated. 3 Open pyeloplasty (OP) is considered the gold standard treatment for UPJO with a > 90% success rate.…”
Section: Introductionmentioning
confidence: 99%
“…An APD of 15-30 mm is an indication for a close follow-up (15). Kandur et al (16) reported that an APD threshold of 20 mm can be used for predicting future obstruction and a low differential renal function (DRF). However, they showed that an APD of 15 mm was not a risk factor for a future low DRF.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal AD, SFU grade (3–4) and AD parenchyma thickness ratio can be considered as the earliest instruments to indicate surgery [25,26]. Postnatal ultrasound cut-off values for renal obstruction on DRS have been suggested to be 15–20 mm AD [27]. Onen’s alternative grading system, of grades 3 or 4 with no jets on a Doppler scan, increased sensitivity to 78.9% and accuracy to 92% in diagnosing obstruction [28].…”
Section: Discussionmentioning
confidence: 99%